Traffic Management Analysis for Video Streaming Service Optimization Using Per Connection Queue (PCQ) Method - Kariyamin; Deyti Lusty A’an; La Ode Alyandi; Adi Imantoyo (PT. Teknologi Futuristik Indonesia, 2025)
Video streaming has become common in everyday life due to its ability to enhance information retrieval and provide an additional dimension to obtaining up-to-date information. However, these benefits are often accompanied by significant bandwidth demands, which can affect network performance. To overcome this challenge, efficient traffic management with separation between browsing and streaming traffic is required. This research addresses network performance issues caused by video streaming services by applying the Per Connection Queue (PCQ) method. This method optimizes streaming video quality while managing network traffic by separating traffic between web browsing and video streaming. The test results show that both types of networks exhibit relatively stable performance over different time intervals. The network without PCQ showed constant values in the measurement parameters, even at 720p video quality with a slight increase in packet loss. Similarly, the network with PCQ showed consistent performance at 240p and 360p video quality, with a slight increase in packet loss in scenario 3 with 720p video quality. The Average Index value of 3.666667 indicates that both have